Acrylate formation from CO2 and ethylene: catalysis with palladium and mechanistic insight - Stieber, S. Chantal E.; Huguet, Núria; Kageyama, Takeharu; Jevtovikj, Ivana; Ariyananda, Piyal; Gordillo, Alvaro; Schunk, Stephan A.; Rominger, Frank; Hofmann, Peter; Limbach, Michael (Chemical communications, 2015)
We report the first catalyst based on palladium for the reaction of CO2, alkene and a base to form sodium acrylate and derivatives. A mechanism similar to a previously reported Ni(0)-catalyst is proposed based on stoichiometric in situ NMR experiments, isolated intermediates and a parent palladalactone. Our palladium catalyst was applied to the coupling of CO2 with conjugated alkenes.
Gesehen am 23.06.2020
Im Titel ist "2" in CO2 tiefgestellt